Fixed Points Of F-Weak Contractions On Complete Metric Spaces - Wardowski D. (Demonstratio Mathematica, 2014)
In this paper, we introduce the notion of an F-weak contraction and prove a fixed point theorem for F-weak contractions. Examples are given to show that our result is a proper extension of some results known in the literature